Hydrocephalus and hydranencephaly in pediatrics: A comprehensive view and analysis of medico-social challenges (Research, Society and Development, 2024)
Introduction: Hydrocephalus and hydranencephaly are severe neurological conditions characterized by the accumulation of cerebrospinal fluid and the destruction of cerebral hemispheres, respectively. While hydrocephalus allows for surgical intervention and improved quality of life, hydranencephaly typically requires palliative care with no realistic prospects of recovery, raising significant ethical and social issues in managing these conditions. Objective: This article aims to analyze the clinical features, etiology, diagnosis, treatment, and prognosis of these conditions, emphasizing the importance of a humanized approach. Methodology: An integrative literature review methodology involved reading, selection, evaluation, and analysis of 37 articles collected between February and June 2024. Results and Discussions: Since Hippocrates' description, the evolution of understanding and treating these pathologies is vital for brain development and function. Anomalies in cerebrospinal fluid flow require surgical intervention. Ethical issues and complex decisions characterize their treatment, especially in severe cases. Expected outcomes include providing valuable information for healthcare professionals, patients, and families, aiding decision-making, and promoting better clinical outcomes and quality of life, while addressing relevant ethical and social issues, emphasizing the importance of compassion and emotional support. Conclusion: Treatment decisions must consider clinical, ethical aspects, and family preferences, requiring a multidisciplinary approach to support patients and families, alleviating suffering and social burden involved.